Ações socioambientais de preservação ante a pressão urbana sobre o patrimônio paisagístico do Sítio do Físico, São Luís-MA - Soares, Bruno Cesar Dias (2021)
The Sítio do Physico is a ruined factory complex, whose buildings date from the end of the 18th century. In 1980, it was recognized by IPHAN as a historical, scenic and archaeological heritage. After the second half of the 20th century, the study area suf- fered urban pressure in its surroundings, with several activities that degraded its land- scape. The research work has the general objective of analyzing socioenvironmental actions for the preservation of landscapes on the Physical Site. For the execution of the research, bibliographical surveys, semi and unstructured interviews, on-site re- search were used. Thematic mappings of Landsat 8 / OLI images, bands 4,3,2 with panchromatic 8 (space-time mapping), images from the ALM satellite (geomorpholog- ical mapping), and environmental vulnerability were also used, using rasters images , processed in Qgis 3.14 (vulnerability letter). The geographic space under study is ge- omorphologically characterized by the features of the river plain and the sea fluvium, in addition to tabular surfaces with dissected hills. The features have a diversity of vegetation cover, with high percentages of environmental vulnerability. In addition, the presence of socioenvironmental impacts in the river channels (contamination of the rivers), in the bottom areas of valleys (garbage on the river plains and marine fluvium), and the thickening of wild fauna, arising from irregular occupations on the Bacanga State Park. In recent decades, the government has established guidelines for preser- vation, such as environmental education, and recreation on the Site and its legal terri- tory. More recently, Law 572/2019 has been discussing the new delimitation of the Park, with implications for the removal of irregular occupations, and the increase of vegetated areas. Consequently, a reduction in urban pressure is expected, followed by a reduction in fresh sewage, but mainly, the redistribution of dense wild animals over the Sítio do Physico to future reforested / recovered areas. On behalf of the Eco- museum, reforestation activities were carried out in SF, environmental education, re- cycling workshops, etc. Through the multitemporal analysis, it was observed an in- crease in the percentage of forested areas, and a reduction in areas of exposed soil, followed by the advance of the urban area towards the study area. The government has historically established several guidelines for the preservation of SF, however, lacking action and implementation. The Ecomuseum is the major player for environ- mental awareness actions and landscape improvements within the study area. How- ever, a broad program of basic sanitation and relocation of families is especially up to the public sphere, which can reduce pressure on the basin, decrease pollution and contamination processes, and also the redistribution of wildlife refugees in the SF.